Postpartum Reproductive Performance Of Kedah Kelantan Cattle And Its Crossbreds - Abdullah, Johari Jiken (1993)

(untitled)
The calving interval of 286 Kedah-Kelantan (KK) cattle and KK crossbreds were obtained from the individual cow breeding records from a crossbreeding project between 1988 to 1990 at Livestock Research Centre MARDI, Kluang, Johore. Postpartum ovarian activity and fertility in 80 suckled cows were studied using clinical observation and progesterone radioimmunoassay. The effect of restricted suckling period on the subsequent reproductive performance of the cows and the growth of their calves were investigated using 46 Kedah-Kelantan and KK cross bred cows.The objectives of these studies were to compare the calving interval and the postpartum ovarian activity and fertility of KK crosses to that of straightbred KK and to evaluate the effect of restricted suckling period on the subsequent reproductive performance of the cows as well as their calves growth performance. The present results showed that the KK and KK crossbred cows had satisfactory reproductive performance. The mean calving intervals of KK, Brahman-KK (BK), Rereford-KK (RK) and Friesian-KK (FK) were 12.6+0.1, 12.4+0. 14, 11.9+0 . 11 and 12.3+0. 14 months, respectively. The first calving interval tended to be the longest, while the fourth, fifth and sixth calving interval tended to be the shortest.